Comparing Percutaneous Coronary Intervention and Coronary Artery Bypass Graft in Treatment of Non-ST-segment Elevation Acute Coronary Syndromes: A Systematic Review and Meta-Analysis Study - Amirmohammad Khalifehsoltani; Enwa Felix Oghenemaro; Ahmed Hussein Zwamel; Rekha M.M; Manish Srivastava; Reza Akhavan-Sigari (PAGEPress Publications, 2024)
Aims: The objective of this study is to compare the effectiveness and safety of percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) in the treatment of non-ST-segment elevation acute coronary syndromes (NSTE-ACS). Methods: A literature search was conducted across PubMed, Scopus, and Web of Science, covering studies up to June 2024. Studies comparing PCI and CABG in patients with NSTE-ACS were included, focusing on clinical outcomes such as mortality, myocardial infarction (MI), cerebrovascular accidents (CVA), and the need for repeat revascularization. Data extraction and quality assessment were performed. Statistical analysis was conducted using R software, with the Mantel-Haenszel method and random-effects model employed to pool effect sizes and assess heterogeneity. Results: A total of 15 studies met the eligibility criteria, including 48,891 patients. The pooled risk ratio (RR) for mortality showed no significant difference between PCI and CABG (RR = 1.09, 95% CI: 0.90-1.19, p = 0.28). CABG was associated with a significantly lower risk of subsequent MI (RR = 0.56, 95% CI: 0.38-0.61, p < 0.01) and the need for repeat revascularization (RR = 2.94, 95% CI: 2.30-3.76, p < 0.01). Conversely, PCI had a lower associated risk of CVA (RR = 0.58, 95% CI: 0.42-0.79, p < 0.01). High heterogeneity was observed in mortality outcomes, indicating variability among studies. Conclusion: The findings suggest that while PCI and CABG have comparable mortality risks in NSTE-ACS patients, CABG offers superior protection against myocardial infarction and the need for repeat revascularization, whereas PCI is associated with a lower risk of cerebrovascular accidents. These results underscore the importance of individualized patient assessment in choosing the optimal revascularization strategy, considering patient-specific risk factors and clinical profiles.